Contrast-Induced Nephropathy and Long-Term Mortality After Percutaneous Coronary Intervention in Patients With Acute Myocardial Infarction. (August 2019) - Sun, Guoli; Chen, Pengyuan; Wang, Kun; Li, Hualong; Chen, Shiqun; Liu, Jin; He, Yibo; Song, Feier; Liu, Yong; Chen, Ji-yan
Abnormal hemodynamics is thought to contribute to the increased risk of contrast-induced nephropathy (CIN) and mortality. However, few studies focused on patients without abnormal hemodynamics (defined as hypotension, intra-aortic balloon pump usage) and reduced left ventricular ejection fraction (LVEF < 40%). Our study was to explore the impact of CIN on mortality in patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI) with relative stable hemodynamics. In this observational study, we included 696 patients with AMI undergoing PCI without reduced LVEF and abnormal hemodynamics. The end point was long-term, all-cause mortality. During the mean follow-up of 2.79 years, CIN was detected in 110 (15.8%) patients. The total all-cause mortality was higher in CIN group than that in non-CIN group (24% vs 3.4%, P < .001). In the multivariate Cox analysis, CIN was an independent predictor of worse outcomes (adjusted hazard ratio [HR]: 2.97, 95% confidence interval: 1.46-6.06, P < .001) and significantly associated with long-term mortality, so did renal insufficiency (adjusted HR: 4.40, P < .001) and use of β-blockers (adjusted HR: 0.33, P < .001). Among patients with AMI, CIN independently predicted long-term mortality following PCI, regardless of LVEF impairment and abnormal hemodynamics.